Escritos Olvidados Del Cuerpo Análisis Psicoanalítico De Los Elementos Inconscientes Que Influyen En El Sujeto Tatuado (2016)
This research presents the theoretical document review, based on the psychoanalytic method and concepts, of the unconscious elements that influence the tattooed subject, which questioned the significance of the rise of the phenomenon, in order to clarify, at the same time, the status of the body in contemporary time and the elements allow the subject unconsciously make indissoluble scriptures in your body. This from a recognition of psychoanalytic theories about the fundamental concepts like ‘body’ and ‘organism’, found explanations based on the registers imaginary, symbolic and real, the implication of writing in the body , the process of repression and the excess of the unconscious, the Oedipus Complex involvement in the writing, and the sublimation involved in this practice.